Philadelphia Paper - Memoranda on the Analysis of Statistics - A. W. Hale (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1881)
In a work published in 1838, De Morgan, the author of the article on " Probabilities," in the Encyclopedia Metropolltimn, says: " The method of least squares is not yet introduced intb the affairs of common life,.....that many things which are denlonstrable only by the higher branches of mathematics are looked upon as useless." And he mentions an instance in which "a method was suggested for estimating the relative importance of boroughs, by considering their population and ~wntributions to the revenue con)-